Short-term anatomic response of the choroid to tropicamide in myopic patients. Issue 37 (16th September 2022) - Lin, Chih-Ying; Wang, I.; Lin, Chun-Ju; Lai, Chun-Ting; Bair, Henry; Chen, Wen-Lu; Lin, Jane-Ming; Tien, Peng-Tai; Hsia, Ning-Yi; Tsai, Yi-Yu
Abstract : We aimed to investigate how tropicamide alters subfoveal choroidal thickness (SFChT) and choriocapillaris flow density (CD) and determine the predictive factors of choroid thickness and vascular density in myopic eyes. This retrospective study was conducted from September 2018 to March 2019. SFChT was measured with enhanced depth spectrum-domain optical coherence tomography. The choriocapillaris was imaged using optical coherence tomography angiograms. Ocular parameters were measured thirty minutes before and after 1% tropicamide instillation. Twenty-five eyes of 15 patients (mean age 38.12 ± 6.35 years old and refractive error-8.57 ± 3.37 D) met the study criteria. The baseline linear regression model showed an association of thinner choroid with older age ( P = .027) and high myopic patients ( P = .001). Tropicamide substantially increased SFChT ( P = .001), but had no significant influence on CD ( P = .526). Moreover, SFChT variation after tropicamide instillation positively correlated with diopter changes in spherical equivalent ( P = .005) and percentage changes in CD ( P = .046). In myopic eyes, choroidal layer thickened substantially in response to tropicamide. The increase of SFChT only correlates with variations in spherical equivalent and CD. Short-term tropicamide installation altered both choroid thickness and choroid microvasculature, which implies an interplay among choroidal volume, perfusion, and ciliary muscle tone.